2018
DOI: 10.3389/fpls.2018.00355
|View full text |Cite
|
Sign up to set email alerts
|

Modify the Histone to Win the Battle: Chromatin Dynamics in Plant–Pathogen Interactions

Abstract: Relying on an immune system comes with a high energetic cost for plants. Defense responses in these organisms are therefore highly regulated and fine-tuned, permitting them to respond pertinently to the attack of a microbial pathogen. In recent years, the importance of the physical modification of chromatin, a highly organized structure composed of genomic DNA and its interacting proteins, has become evident in the research field of plant–pathogen interactions. Several processes, including DNA methylation, cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 176 publications
(215 reference statements)
0
80
0
Order By: Relevance
“…However, it is also known that the excessive and unnecessary activation of immune responses can have detrimental effects on physiology, as evidenced by the existence of several autoimmune mutants, many of which display compromised development and growth (van Wersch et al ., ). Plants must therefore fine tune the expression of stress‐responsive genes, and there is increasing evidence indicating that chromatin dynamics plays a crucial role in this process (Smale et al ., ; Mehta et al ., ; Probst and Mittelsten Scheid, ; Espinas et al ., ; Lämke and Bäurle, ; Ramirez‐Prado et al ., ,b). The characterization of mutants for various chromatin modifiers has elucidated the role of several of these proteins in the regulation of both developmental and stress‐responsive pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also known that the excessive and unnecessary activation of immune responses can have detrimental effects on physiology, as evidenced by the existence of several autoimmune mutants, many of which display compromised development and growth (van Wersch et al ., ). Plants must therefore fine tune the expression of stress‐responsive genes, and there is increasing evidence indicating that chromatin dynamics plays a crucial role in this process (Smale et al ., ; Mehta et al ., ; Probst and Mittelsten Scheid, ; Espinas et al ., ; Lämke and Bäurle, ; Ramirez‐Prado et al ., ,b). The characterization of mutants for various chromatin modifiers has elucidated the role of several of these proteins in the regulation of both developmental and stress‐responsive pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of mutants for various chromatin modifiers has elucidated the role of several of these proteins in the regulation of both developmental and stress‐responsive pathways. Several epigenomic regulators with diverse functions, including histone mark writers, readers and erasers, were identified as positive and negative regulators of immunity, or shown to play an important role in the regulation of the interplay between the diverse hormonal pathways that constitute the plant immune system (Bu et al ., , Ding and Wang, ; Espinas et al ., ; Ramirez‐Prado et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, members of the Trithorax Group (TrxG), known to catalyze H3K4 and/or H3K36 methylation play pivotal roles in promoting RNA polymerase II (RNAPII) transcription and were demonstrated to control key phase transitions and important stages related to plant development (for a review, see Berr et al, 2011Berr et al, , 2016Fletcher, 2017). In addition, some TrxG members are also involved in plant defense against pathogens (for review see Bobadilla and Berr, 2016;Ramirez-Prado et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of defence pathways often requires massive transcription reprograming, resulting in altered gene expression and chromatin mark deposition at defence‐associated loci (Espinas et al , ; Li et al , ). Histone modifications potentially provides a reversible and dynamic way to regulate many biological processes including plant immunity (Ramirez‐Prado et al , ). In Arabidopsis, histone deacetylase HDA6 (Wang et al , ), HDA19 (Zhou et al , ; Choi et al , ), methyltransferases ATX1 (Alvarez‐Venegas et al , ), ATXR7 (Xia et al , ), SDG8 (Berr et al , ) and SDG25 (Lee et al , ), demethylases FLD (Singh et al , ) and JMJ27 (Dutta et al , ), and H2B monoubiquitinase HUB1 (Dhawan et al , ; Zou et al , ), have been previously shown to affect plant resistance.…”
Section: Discussionmentioning
confidence: 99%